Efforts to Improve Memorization of Hadith About Taqwa Through the Application of the Drill Method in Grade 4 Students of Al-Wathoniyah Ciasem Subang Elementary School - Pujiwati; Herdi, Asep (Department of Teacher Professional Education, Tarbiya and Teacher Training Faculty, UIN Sunan Gunung Djati Bandung, 2024)
This study aims to improve the memorization of hadiths on piety among 4th-grade students at Madrasah Ibtidaiyah Al-Wathoniiyah Ciasem Subang through the application of the drill method. The drill method is a learning technique that emphasizes systematic and intensive repetition, believed to be effective in enhancing students' memory retention for memorized material. This research employs the Classroom Action Research (CAR) method with four stages: planning, action, observation, and reflection. The subjects of the study are 25 fourth-grade students. The results indicate that the application of the drill method significantly improves students' ability to memorize hadiths on piety. This is evidenced by an increase in the average test scores of students' memorization results from the first to the second cycle. Additionally, students showed increased motivation and active participation in the learning process. The drill method not only helps students memorize faster but also strengthens their understanding of the content of the hadiths they memorize. Therefore, the implementation of the drill method has proven effective in improving the memorization of hadiths on piety among madrasah students. This method can serve as an alternative that teachers can adopt in teaching hadith memorization, particularly at the elementary school level.